Human impact on small-mammal diversity during the middle- to late-Holocene in Iberia: The case of El Mirador cave (Sierra de Atapuerca, Burgos, Spain) - Bañuls-Cardona, Sandra (2017)
The human impact on the environment in the Holocene has usually been characterized on the basis of palaeobotanical records, but attempts to distinguish the anthropogenic impact from natural events in landscape evolution have been the subject of much debate in recent years. The aim of this paper is to analyse small-mammal diversity and the presence of synanthropic species, whose small size makes them more sensitive to any changes in their environment that may occur. This study has allowed us to characterize palaeoclimatic and palaeoenvironmental changes, recording small changes whether resulting from a human influence or otherwise. Our object of study is El Mirador cave, which has a sequence with a well-documented human occupation extending from 7200 to 3000 cal. BP. The study has led us to differentiate two phases. In one phase, we can see small changes in diversity related to climatic oscillations from ca. 7200 to 6800 cal. BP, while in the second phase, lasting from ca. 6800 to 3000 cal. BP, the changes in diversity and in the assemblage of synanthropic species are associated with human economic strategies. Moreover, we distinguish which kinds of economic activity (crop and livestock farming) have influenced these changes, because some small-mammal species are influenced, positively or negatively, by environmental changes based on crop farming and animal husbandry. All this information is contrasted with other archaeological proxies, such as the large-mammal and palaeobotanical assemblages from El Mirador cave. Furthermore, this integrative analysis has made it possible to identify the existence of altered environments more generally throughout the Iberian Peninsula from ca. 6000 cal. BP. It additionally confirms the theory of low human occupation intensity in the northern Meseta and in high mountainous areas during the early Neolithic.